PENERAPAN PSBB DI KOTA DENPASAR DALAM MENGANTISIPASI COVID-19 - Putrawan, I Nyoman Alit (VYAVAHARA DUTA, 2021)
Denpasar, as one of the cities in Bali which is famous for its tourism industry, has participated in implementing PSBB. This is stated in the Governor of Bali Instruction Number 8551 of 2020 which contains the strengthening and prevention of COVID-19. Through the instructions of the Bali governor, Denpasar has taken various steps to reduce the number of exposure to COVID-19, such as implementing discipline in health protocols, working from home, studying online from home and praying at home. This research is a normative legal research. The results of this paper explain that the implementation of the Large-Scale Social Restrictions policy (PSBB) in dealing with the Covid 19 outbreak in Denpasar City is based on Government Regulation Number 21 of 2020 concerning PSBB and Bali Governor Instruction Number 8551 of 2020 which contains the strengthening and prevention of COVID-19, regulations regarding restrictions on transportation, social, and physical mobilization of the community due to the spread of disease, which are regulated in Law Number 6 of 2018 concerning Health Quarantine. These various policies then outlined by the Denpasar City Government in the form of Denpasar City Mayor Number 32 of 2020 concerning Limiting Community Activities in Villages, Sub- Districts and Traditional Villages in the Acceleration of Handling COVID-19.Keywords: PSBB; Policy; Handling; Covid-19.